Living with seismic phenomena in the Mediterranean and beyond between antiquity and the Middle Ages : proceedings of Cascia (25-26 October, 2019) and Le Mans (2-3 June, 2021) conferences - Compatangelo, Rita; Diosono, Francesca; Le Blay, Frédéric (Archaeopress Archaeology, 2022)
In a Mediterranean area characterised by strong seismic activity, the earthquake that struck central Italy in 2016 caused considerable damage to the archaeological and historical heritage. This catastrophic event, as well as recent archaeological fieldwork and palaeoseimological research in the same area, led to the organisation in 2019 of the first International Conference Living with seismic phenomena in the Mediterranean from Antiquity to the Middle Ages in Cascia (Italy). In 2021, a second Conference, devoted to the same topic, was held at Le Mans University (France). The articles collected in this work constitute a selection of the oral presentations or posters presented during the two Conferences.